Conflict at the heartland: Investigating the nexus between nomadic herdsmen/farmers clashes and socio-economic dynamics in Benue State (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Farmer-herder conflicts in Nigeria, particularly in Benue State, have escalated over the past decade, leading to significant socio-economic and security challenges. Despite media and research attention, effective political responses have been lacking, exacerbating the crisis. This study aimed to investigate the impact of nomadic herdsmen-farmers conflicts on food production and the security of lives and property in Benue State, Nigeria. A Survey Research Design was utilized, with a sample size of 400 determined using the Taro Yamane formula.Multi-stage sampling was employed to select respondents from four LGAs with high conflict levels. Data analysis involved using simple linear regression to evaluate the relationship between the conflict and both food production and security. The study found a significant relationship between nomadic herdsmen-farmers conflict and both food production and the security of lives and property. The conflict explained 6.4% and 8.3% of the variance in food production and security, respectively, with moderate joint linear associations confirmed by ANOVA. Thefindings underscore the urgent need for targeted interventions to mitigate the impact of conflicts on agriculture and enhance security measures in affected areas. Empowering local communities and diversifying livelihoods are crucial strategies to address the complex dynamics of these conflicts.
Keywords: Farmer-herder conflicts; nomadic herdsmen; food production; security; Benue State